Stimulasi kemampuan komunikasi matematis siswa SMP menggunakan pendekatan realistic mathematics education untuk mendukung profil pelajar pancasila - Puspita, Widianti; Pertiwi, Citra Megiana; Hidayat, Wahyu (IKIP Siliwangi, 2025)
This research aims to stimulate mathematical communication skills in statistics for junior high school students using a realistic mathematics education approach to support the Pancasila student profile. In this research, the researcher chose a quasi-experimental research method. The population in this study were all class VIII students in one of the junior high schools in the city of Bandung, and two classes were used as research samples selected by purposive sampling. The first class was made into an experimental class using the RME approach. The second class was used as a control class whose learning used ordinary learning. The results of this study show that 1) There is a positive correlation between the Pancasila student profile and mathematical communication skills in experimental class students, this is because the mutual cooperation dimension in P5 emphasizes communication skills. 2) students' mathematical communication skills increase from the low category to the high category. 3) the students' characters are more similar to Pancasila students after being taught mathematics with a realistic approach.